Gender Contribution to the Utilization of Social Forestry in Central Aceh Regency - Seli Nardatila; Dahlan; Elvira Iskandar (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Social forestry aims to improve people's well-being through community-based forest management, but there is still a gap in participation and contribution between men and women. This study analyzes the level of gender participation and contribution in the use of social forestry in Central Aceh Regency. A quantitative approach with purposive sampling techniques was used, involving 207 respondents from the Village Forest and Community Forest schemes. The results showed that the participation of men was very high (score of 32.65) while the participation of women was high (28.42). The outpouring of working time for men is 11.2 hours/day, for women 13.5 hours/day with a double workload. Male net income is IDR 1,003,000/month and female IDR 637,000/month, with a contribution to family income of 25.95% and 22.60% respectively. Strengthening the role of institutions, inclusive training for women, and gender-responsive policies are needed to realize sustainable and equitable forest management